1908
DOI: 10.5962/bhl.title.54917
|View full text |Cite
|
Sign up to set email alerts
|

Elements of water bacteriology, with special reference to sanitary water analysis

Abstract: Elements of Water Bacteriology.Certain bacteriologists have held that the toxic waste products of the bacteria themselves may render water unfit for their own development. Horrocks (Horrocks, 1901), Garr^(Garrd, 1887), Zagari (Zagari, 1887), and Freudenreich (Freudeiureich, 1888) have shown that an "antagonism" exists when bacteria are grown in artificial culture media such that the substratum which has supported the growth of one form may be rendered antiseptic to another. Frost (1904) has exhaustively stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…(Taj and Baqai, 2007). Similarly, alum was not an effective killing agent for cholera organisms (Prescott et al, 1997). Another study reported that alum significantly reduced bacteria, but it did not kill or destroy typhoid and cholera organisms (Prescott et al, 1997).…”
Section: Coagulative Effect Of Plant Extracts and Alum On Untreated Wmentioning
confidence: 96%
“…(Taj and Baqai, 2007). Similarly, alum was not an effective killing agent for cholera organisms (Prescott et al, 1997). Another study reported that alum significantly reduced bacteria, but it did not kill or destroy typhoid and cholera organisms (Prescott et al, 1997).…”
Section: Coagulative Effect Of Plant Extracts and Alum On Untreated Wmentioning
confidence: 96%
“…The following admonition by Prescott and Winslow (1904) should be kept in mind by any investigator who attempts to use microbiological data obtained from water: The quest for a mathematical relationship between pathogens and other nonpathogenic microorganisms began as soon as results on microbial concentrations were obtained from various water types.…”
Section: Introductionmentioning
confidence: 99%
“…The survival and concentration of E. coli in the floc suggested the presence of other pathogenic enteric organisms (Bulson et al 1984). Another study reported that alum significantly reduced bacteria but it did not kill or destroy the greater strength of typhoid and cholera organisms (Prescott et al 1997).…”
Section: Antibacterial Activity Against Waterborne Pathogensmentioning
confidence: 99%